CULTIVATING SUPPORT THROUGH EFFECTIVE COMMUNICATION BETWEEN A MEDICAL TEAM AND A CANCER PATIENT – CASE REPORT - Banovic, Svetlana (Medicinski časopis, 2016)
Introduction: In the contemporary, holistic approach to cancer treatment, it is of the utmost importance that health professionals apply all aspects of a supportive relationship in communication with the patient and his/her family. An adequate, high-quality communicative approach through a coordinated relationship among all members of the cancer treatment team based on respect for communication skills, empathy, and psychological and spiritual support enables assessment of psychosocial needs and spiritual support to the patient and improves the success rate of the diagnostic and therapeutic procedures. In order to make the communication effective, the patient should be allowed to freely express feelings, worries and fears. The implementation of appropriate and individualized communication with the patient results in the identification and resolution of a series of interfering and disabling factors that compromise a positive therapeutic outcome. Insofar as it is continuous and always available, high-quality communication achieved through positive interaction between members of the medical team and the cancer patient and his/her family can contribute to the patient’s feeling of renewed merit and courage in facing all the challenges of a malignant disease. Case outline: This paper presents a case report as an example of good communication between a patient suffering from breast cancer and a cancer treatment team, which was achieved during and after radiation therapy. The health professionals’ quality consultative and educational approach to the patient and her family throughout the time of crisis contributed to the resolution of the patient’s current problems and consequently to the success of the cancer treatment. The development of an anxiety disorder in the patient was prevented, while increasing her self-awareness and achieving her psychophysical stability in dealing with the challenges of the malignant disease and its treatment. Conclusion: Adequate communication and a supportive psychological approach between the medical team and the patient/family during oncological treatment are of tremendous importance, and represent one of the major factors necessary to achieve a positive outcome of diagnostic and therapeutic procedures. Specific educational approaches of all members of a cancer treatment team in this context would highly contribute to the success achieved and mutual satisfaction of healthcare professionals and patients.